Rainfall-runoff process and groundwater recharge in the Upper Blue Nile Basin: the case of Dangishta Watershed - Yimam, A. Y.; Bekele, A.M.; Nakawuka, Prossie; Schmitter, Petra S.; Tilahun, Seifu A. (Springer, 2019)
For planning, development and management of water resources, understanding runoff mechanism and groundwater recharge is useful especially to watershed management and groundwater use for domestic and irrigation water supply. During the period of the study, stream flow, groundwater levels, infiltration tests, rainfall and soil moisture measurements were conducted. The result from these measurement showed that saturation excess runoff were dominant in Dangishta watershed while infiltration excess runoff also contributes in some parts of the upslope area. This result was also corroborated by better correlation of (R2 = 0.82) at the main outlet than upstream sub watershed outlet (R2 = 0.56) using SCS runoff equation. The result from groundwater level measurement using water table fluctuations approach showed that the total annual groundwater recharge were found to be 400 mm (i.e. 24% of the total annual rainfall) which is a significant amount likely because of the interflow processes to each well.